Analisis Determinan Perilaku Keuangan Guru Honorer Sekolah Dasar Di Kecamatan Karang Tengah Kota Tangerang - Wahyudi, Wahyudi; Tristiarto, Yoko (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
This study is a quantitative study that aims to determine the effect of financial literacy, financial technology, and income on financial behavior. The population in this study were honorary elementary school teachers in the district of Karang Tengah, Tangerang city. Samples were taken as many as 80 respondents, with non-probability sampling method, purposive sampling. Data was collected through the distribution of questionnaires. The analytical technique used is the PLS (Partial Least Square) analysis method with SmartPLS 3.0 software. The results of this study indicate that (1) financial literacy has a significant positive effect on financial behavior. (2) financial technology has no influence and is not significant on financial behavior. (3) income has a significant positive effect on financial behavior.